Preloading hydrous ferric oxide into granular activated carbon for arsenic removal - Jang, M.; Chen, W.; Cannon, F.S. (2008)
Arsenic is of concern in water treatment because of its health effects. This research focused on incorporating hydrous ferric oxide (HFO) into granular activated carbon (GAC) for the purpose of arsenic removal. Iron was incorporated into GAC via incipient wetness impregnation and cured at temperatures ranging from 60 to 90 °C. X-ray diffractions and arsenic sorption as a function of pH were conducted to investigate the effect of temperature on final iron oxide (hydroxide) and their arsenic removal capabilities. Results revealed that when curing at 60 °C, the procedure successfully created HFO in the pores of GAC, whereas at temperatures of 80 and 90 °C, the impregnated iron oxide manifested a more crystalline form. In the column tests using synthetic water, the HFO-loaded GAC prepared at 60 °C also showed higher sorption capacities than media cured at higher temperatures. These results indicated that the adsorption capacity for arsenic was closely related to the form of iron (hydr)oxide for a given iron content. For the column test using a natural groundwater, HFO-loaded GAC (Fe, 11.7) showed an arsenic sorption capacity of 26 mg As/g when the influent contained 300/μg/L As. Thus, the preloading of HFO into a stable GAC media offered the opportunity to employ fixed carbon bed reactors in water treatment plants or point-of-use filters for arsenic removal. © 2008 American Chemical Society.